A case of tape infection 19 years after insertion of a tension‐free vaginal tape sling. Issue 4 (28th March 2022) - Watanabe, Tomofumi; Sako, Tomoko; Tominaga, Yusuke; Sadahira, Takuya; Sekito, Takanori; Takamoto, Atsushi; Edamura, Kohei; Kobayashi, Yasuyuki; Wada, Koichiro; Araki, Motoo
Abstract : Introduction: Tape infection after insertion of tension‐free vaginal tape is a well‐known but rare complication. We report a patient who experienced a subcutaneous abscess 19 years after the surgery. Case presentation: A 41‐year‐old woman presented with fever and lower abdominal pain. She had undergone tension‐free vaginal tape insertion for stress urinary incontinence 19 years prior. She had asymptomatic dysuria. After an abscess incision and 1‐week treatment with antibiotics, she underwent surgery to remove the tape and the abscess without complications. Conclusion: Tension‐free Vaginal Tape insertion could be a potential risk of asymptomatic dysuria, resulting in urinary tract infection. In this case, removal of tape was necessary for controlling subcutaneous abscess resulting from the presence of tension‐free vaginal tape.